Juggling with Languages: Multilinguals’ Beliefs and Experiences of Translanguaging and Code-Switching - Akhmerova, R.; Kenshinbayeva, A.; Toktamyssova, A. (M. S. Narikbayev KAZGUU University School of Liberal Arts, 2023)
Due to the increased popularity of Multilingualism both worldwide and in Kazakhstan, scholars have become more interested in researching Multilinguals’ experiences and beliefs on certain multilingual practices, namely Translanguaging and Code-Switching. However, the existing studies tend to explore these concepts from an educational perspective. Hence, there is an insufficient amount of research available on Multilinguals' experiences and beliefs of Translanguaging and Code-Switching in a Social context. Moreover, the majority of the studies do not encompass both Translanguaging and Code Switching, but rather study them separately, hence, insufficient data is available on the similarities and differences between Multilinguals' experiences and beliefs of Translanguaging and Code-Switching. Thus, this research aims to study Multilinguals’ practices and attitudes toward Translanguaging and Code-Switching from both Academic and Social perspectives, and also identify whether Multilinguals’ Translanguaging and Code-Switching practices and attitudes are similar or different. To study this, several research questions have been proposed: 1. What are Multilinguals’ experiences of Translanguaging and Code-switching? 2. What are Multilinguals’ beliefs on Translanguaging and Code-switching? 3. How are Multilinguals’ experiences and beliefs on Translanguaging similar or different from the ones on Code-switching? This is qualitative phenomenological research that studies the phenomena of Translanguaging and Code-Switching as well as Multilinguals’ experiences and beliefs on the established phenomena. The findings were obtained through semi-structured interviews and then triangulated through observations. Participants of the current study come from similar educational and social multilingual backgrounds. Purposeful and criterion sampling strategies were implemented to select Participants who are knowledgeable in the studied phenomena, actively practice teaching English, and are Multilinguals. The findings of the research showed that Multilnguals’ have controversial perspectives on Translanguaging and Code-Switching, and these beliefs are correlated with their practices of the aforementioned techniques. Moreover, certain similarities and differences in the implementation and perception of Translanguaging and Code-Switching were discovered
Keywords: Translanguaging, Code-Switching, Multilingualism, Multilinguals, Multilinguals’ experiences and beliefs, Academic and Social environments